Human TYK2 deficiency: Mycobacterial and viral infections without hyper-IgE syndrome - Kreins, Alexandra Y.; Ciancanelli, Michael J.; Okada, Satoshi; Kong, Xiao-Fei; Ramirez-Alejo, Noe; Kilic, Sara Sebnem; El Baghdadi, Jamila; Nonoyama, Shigeaki; Mahdaviani, Seyed Alireza; Ailal, Fatima; Bousfiha, Aziz; Mansouri, Davood; et al. (Journal of Experimental Medicine, 2015)
Autosomal recessive, complete TYK2 deficiency was previously described in a patient (P1) with intracellular bacterial and viral infections and features of hyper-IgE syndrome (HIES), including atopic dermatitis, high serum IgE levels, and staphylococcal abscesses. We identified seven other TYK2-deficient patients from five families and four different ethnic groups. These patients were homozygous for one of five null mutations, different from that seen in P1. They displayed mycobacterial and/or viral infections, but no HIES. All eight TYK2-deficient patients displayed impaired but not abolished cellular responses to (a) IL-12 and IFN-?/?, accounting for mycobacterial and viral infections, respectively; (b) IL-23, with normal proportions of circulating IL-17(+) T cells, accounting for their apparent lack of mucocutaneous candidiasis; and (c) IL-10, with no overt clinical consequences, including a lack of inflammatory bowel disease. Cellular responses to IL-21, IL-27, IFN-?, IL-28/29 (IFN-?), and leukemia inhibitory factor (LIF) were normal. The leukocytes and fibroblasts of all seven newly identified TYK2-deficient patients, unlike those of P1, responded normally to IL-6, possibly accounting for the lack of HIES in these patients. The expression of exogenous wild-type TYK2 or the silencing of endogenous TYK2 did not rescue IL-6 hyporesponsiveness, suggesting that this phenotype was not a consequence of the TYK2 genotype. The core clinical phenotype of TYK2 deficiency is mycobacterial and/or viral infections, caused by impaired responses to IL-12 and IFN-?/?. Moreover, impaired IL-6 responses and HIES do not appear to be intrinsic features of TYK2 deficiency in humans.
EVALuna2:8293